(3GdUchc cCOGI ddJehjd habkG dbGfhf Qbe (B10(3dSfI (B2013/ s - (3dHfi YeGO eMeO YHOGdYRjRs; (3SejMI eUWai GdbdjhHi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3jSJgOa GdHMK OQGSI h JMdjd GdfXGe GdJTQjYi ddUchc Ydi VhA GdbGfhf GdMGdi h ai GdJTQjYGJ GdebGQfI(B: (3h jegO GdHMK Edi gOag HGdJYQja Ydi eGgjI GdUchc h CfhGYgG h NUGFgG(B: (3h ChLg GNJdGagG h GJaGbgG eY HYV COhGJ GdJehjd GdJbdjOjI aCSS EUOGQgG h JOGhdgG(B. (3ceG jgOa GdHMK Edi GdJYQa Ydi JLGQH EUOGQ gPg GdUchc Ydi eSJhi GdOhd(B: (3eY YQV LGfH ef GdeTcdGJ GdJi hGLgJgG(B: (3h OQGSI GdEWGQ GdJTQjYi GddGRe dJaYjd GdJYGed HGdUchc h YQVgG dJYOjd JTQjYi dbGfhf GdUchc(B. (3h bSeJ GdQSGdI Edi aUdjf GdChd eNUU ddJYQa Ydi eGgjI GdUchc HUhQI YGeI eY EHQGR eG JJeJY Hg ef eRGjG h NUGFU eJfhYI Edi LGfH GdebGQfI HjfgG h Hjf COhGJ GdJehjd GdCNQi(B. (3HjfeG YGdL GdaUd GdKGfi(B: (3CSS EUOGQ GdUchc h bhGYO h CMcGe JOGhdgG eY YQV LGfH ef JLGQH HYV GdOhd GdeUOQg dUchc eeGKdgs
(3jTJed Ydi edGMb(B: (3UaMGJ (B180-200s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2016s
(3HHdjhLQGajG(B: (3UaMGJ (B164-178s
Keywords: (3GdbGfhf GdJLGQjs; (3GdUchc GdJLGQjIs; (3Uchc GdJehjd hUchc GdGLGQIs; (3Uchc GdGSJKeGQs; (3Uchc GdeTGQcI ai GdGfJGLs; (3GdJUcjc s; (3GdLgGJ GdJj dgG Mb GUOGQ GdUchcs; (3JLGQH GdOhd GdGSdGejI h GdUchc (B((3GdJLQjI GdeGdjRjI (B) ( (3GdJLQHI GdGeGQJjI(B) ( (3GdJLQjI GdSYhOjI(B)s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs